Deferitazole, a new orally active iron chelator1. Issue 11 (21st March 2015) - Hider, Robert C.; Kong, Xiaole; Abbate, Vincenzo; Harland, Rachel; Conlon, Kelly; Luker, Tim
<x xml:space="preserve">Abstract</x> Deferitazole possesses a high affinity and selectivity for iron(iii), forming an equilibrium mixture of two FeIII(deferitazole)2 complexes, under biological conditions.